INTERTEXTUAL STUDY OF MY LOVING POEMS AWAY ON ISLAND WORK CHAIRIL ANWAR WITH FANA'S POETRY IS TIME WORK BY SAPARDI DJOKO DAMONO WITH SYNTAX ANALYSIS - Mimin Sahmini (JLER (Journal of Language Education Research), 2018)
The text of both literary and non-literary texts is born not from a cultural vacuum, but the text is born because there is a relationship between living conditions with economic, social, political, and cultural values that are expressed in writing and using language as the medium. Thus language has an important role for the birth of a text. Intertext is an ongoing quest for meaning. Penelususran meaning is done outside the work of the individual, not limited by space and time. The speaking subject is subject to subject, as the subject of the text, not the author in fact. The meaning in literary works can be obtained through analysis by heeding literary works from historical context and socio-cultural context in this intertextual concept related to literary history. Thus, the text is the product of the historical social forces of its day, but the text also affects social life. Poetry is one of the works of literature is poured with beautiful language, in this study the author wanted to know the intertextual poetry of Chairil Anwar entitled Cintaku Jauh on the Island with the poem Sapardi Djoko Damono with the title The Fana is Time . In this analyze, method used in this study is qualitative by analyzing every word chosen in the poem with the syntactic aspect. The main purpose is to describe, study and explain the phenomenon. Understanding this phenomenon can be obtained by describing and exploring it in narrative writing. The intertextual study in both poems has the similarity that in real life we have to make the best use of time, because God's destiny no one knows when we should return to God's bosom as described by Khairil Anwar in his poetry how I lyrics pursue his life to achieve the goal -ltanya, but the I feel pessimistic will be achieved his goal is because the I'm sure with the fate of his death is quite close.